Immunotherapy with cat- and dog-dander extracts: V. Effects of 3 years of treatment - Hedlin, G.; Graff-Lonnevig, V.; Heilborn, H.; Lilja, G.; Norrlind, K.; Pegelow, K.; Sundin, B.; Lowenstein, H. (Journal of allergy and clinical immunology, 1991)
The effect of a 3-year course of cat or dog immunotherapy (IT) was evaluated in 32 patients with a history of asthma on exposure to cat or dog. Twenty-one subjects (14 children and seven adults) received cat IT and 11 subjects (six children and five adults) received dog IT. Bronchial challenges with allergen and histamine were performed once a year. Specific IgE, IgG1, and IgG4 were measured, and skin prick tests were done in connection with the challenges. Allergen sensitivity decreased significantly in both treated groups ( p < 0.001 and p < 0.05 in the cat-allergen and dog-allergen treated groups, respectively). Bronchial hyperreactivity measured by the provocative concentration of histamine causing a 20% decrease in peak expiratory flow in the cat-allergen treated patients p < 0.001) but not in the dog-allergen treated patients. Skin sensitivity decreased in both groups ( p < 0.01 and p < 0.05), whereas specific IgE increased initially but dropped to the pretreatment level during the second year. Specific IgG1 and IgG4 increased during the first and second year in the cat-allergen treated group ( p < 0.01 and p < 0.001), whereas only IgG4 increased in the dog-allergen treated group ( p < 0.01). Five cat-allergen treated children and one of the adults who completed 3 years of therapy had mild systemic reactions. We conclude that cat IT ameliorated bronchial allergen sensitivity and bronchial hyperreactivity and resulted in an adequate antibody response. Dog IT was less efficacious but led to attenuation of bronchial allergen sensitivity.